2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1424.r2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of patient point of entry and Medicaid status on quality outcomes following total hip arthroplasty

Abstract: Aims Previous studies have reported an increased risk for postoperative complications in the Medicaid population undergoing total hip arthroplasty (THA). These studies have not controlled for the surgeon’s practice or patient care setting. This study aims to evaluate whether patient point of entry and Medicaid status plays a role in quality outcomes and discharge disposition following THA. Methods The electronic medical record at our institution was retrospectively reviewed for all primary, unilateral THA betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…23 Furthermore, public health insurance patients carry higher odds of requiring acute medical care within 30 days after ACLR. 32 Studies investigating the impact race/ethnicity and insurance status have on postoperative complications have reported similar findings among orthopaedic [70][71][72][73][74] and spine 75,76 patients. These findings emphasize the disparity in access to care between patient populations experiencing social deprivation or social support as the result of their SDOH, which directly affect outcomes after ACLR.…”
Section: Discussionmentioning
confidence: 84%
“…23 Furthermore, public health insurance patients carry higher odds of requiring acute medical care within 30 days after ACLR. 32 Studies investigating the impact race/ethnicity and insurance status have on postoperative complications have reported similar findings among orthopaedic [70][71][72][73][74] and spine 75,76 patients. These findings emphasize the disparity in access to care between patient populations experiencing social deprivation or social support as the result of their SDOH, which directly affect outcomes after ACLR.…”
Section: Discussionmentioning
confidence: 84%
“… 22 , 23 , 24 , 25 More specifically, recent investigations have demonstrated that in those undergoing total joint arthroplasty of the hip, knee, or shoulder, patients with Medicaid have greater resource use, greater complication rates, and poorer postoperative outcomes. 8 , 10 , 13 , 14 , 23 , 26 , 27 With the expansion of Medicaid through the Affordable Care Act in 2014, the investigation of these disparities in one of the most common orthopaedic sports medicine procedures performed, ACL reconstruction, is critical. 23 …”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] More specifically, recent investigations have demonstrated that in those undergoing total joint arthroplasty of the hip, knee, or shoulder, patients with Medicaid have greater resource use, greater complication rates, and poorer postoperative outcomes. 8,10,13,14,23,26,27 With the expansion of Medicaid through the Affordable Care Act in 2014, the investigation of these disparities in one of the most common orthopaedic sports medicine procedures performed, ACL reconstruction, is critical. 23 When assessing our primary outcome, despite similar preoperative IKDC scores (53.65 vs 53.95; P ¼ .978) between the 2 cohorts, we found significantly lower postoperative IKDC scores (P ¼ .005) at final follow-up in patients with Medicaid insurance compared with those with private insurance (74.68 vs 90.45, respectively; P ¼ .005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic disadvantage has been associated with higher mortality rates after THA. [20][21][22] Rhee et al 23 reported increased risk for mortality with blood transfusions (OR 2.6; 95% CI, 1.3-5.3), myocardial infarction (OR 7.9; 95% CI, 2.6-24. Obesity has been associated with mixed results in regard to mortality after THA.…”
Section: Risk Factors For Mortalitymentioning
confidence: 99%